Susan Clayton Oral History Interview, 2022 - Duke University. Medical Center. Department of Surgery. (2022)
This oral history interview was conducted with Susan Clayton on February 21, 2022 by Taylor Patterson as part of the Dr. David Sabiston Oral History Project. During the interview, Clayton discusses her background; becoming a single parent and having to find work to support her two young daughters; getting hired as a Staff Assistant in the Department of Surgery and later discovering she was the only applicant because of Sabiston's reputation; Sabiston's high expectations of the office staff and all people who worked for him, which lead to a high turnover rate; her experiences as the Residency Coordinator; the supportive nature of the Department of Surgery office staff; details of her roles in the Department of Surgery and other Staff Assistants; having to work three Saturdays a month; and other memories of Sabiston.